2014
DOI: 10.1177/1054773813516789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Family Involvement Program in Patients With Central-Line Insertion

Abstract: The purpose of this study was to evaluate the effects of family-involved care on caregivers' self-efficacy, the degree of satisfaction with central-line care, and the occurrence of central-line-associated bloodstream infections (CLABSIs). We adopted a pretest-posttest quasi-experimental design, recruiting 62 participants from 2009 to 2010. Family caregivers in the experimental group received instructional guidance before collaboratively participating in patient care, whereas the control group received routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…When engaging patients and families in an interdisciplinary task or at the organization level (Ahmadi et al., 2022; Dunn et al., 2017; Lawton et al., 2017), it is efficient and necessary to implement interventions through multidisciplinary teamwork. Some other studies were carried out by other unconventional stakeholders, such as trained research assistants, investigators or volunteers (Cho & Lee, 2021; See et al., 2011; Shin et al., 2021; Tan et al., 2015), but it is difficult to integrate these interventions into routine medical practice and achieve ongoing PFE. Finally, adequate preparation and training for involved HCPs prior to engaging patients and families can assure effective PFE (Cox et al., 2017; Opsahl et al., 2017), but now only one in four studies reported that they conducted this work.…”
Section: Discussionmentioning
confidence: 99%
“…When engaging patients and families in an interdisciplinary task or at the organization level (Ahmadi et al., 2022; Dunn et al., 2017; Lawton et al., 2017), it is efficient and necessary to implement interventions through multidisciplinary teamwork. Some other studies were carried out by other unconventional stakeholders, such as trained research assistants, investigators or volunteers (Cho & Lee, 2021; See et al., 2011; Shin et al., 2021; Tan et al., 2015), but it is difficult to integrate these interventions into routine medical practice and achieve ongoing PFE. Finally, adequate preparation and training for involved HCPs prior to engaging patients and families can assure effective PFE (Cox et al., 2017; Opsahl et al., 2017), but now only one in four studies reported that they conducted this work.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited data exist regarding central venous catheter issues in those with AKI-D, much can be learned from investigations in other populations with central venous catheters. 47 , 48 Patients with AKI-D should receive training about vein preservation. Delivery of these educational components is an excellent example of an important and easy quality measure for health systems and dialysis facilities to track.…”
Section: Statement 1: To Optimize the Care Of Patients With Aki Or Akmentioning
confidence: 99%